The Influence of Children’s Educational Value and Gender Responsive Education Parenting towards Adolescent Interest in Continuing Higher Education During Covid-19 Pandemic - Azzahraa, Nur Pattimah; Puspitawati, Herien (Journal of Family Sciences, 2024)
The Covid-19 pandemic has resulted in socioeconomic changes that have decreased interest in continuing higher education. This study aimed to analyze the influence of children’s educational value and gender-responsive education parenting toward adolescent interest in continuing higher education during the Covid-19 Pandemic. This study used a cross-sectional design and a non-probability purposive sampling method. Data were collected in May 2022, with a total of 40 male and 40 female adolescents from four public high schools in the Brebes Regency. This study used descriptive analysis, t-tests, correlation, and path analysis with the SEM-PLS model. The results found that There were no significant differences between the variables studied in the sample of male and female adolescents. Based on a correlation test, there was a significant relationship between the core variables. The SEM-PLS model shows that gender has a significant influence on children’s educational value and interest in continuing higher education. Other results show that children’s educational value has a significant effect on their interest in continuing higher education. This study implies that interest in continuing higher education can be increased by increasing children’s educational value.